Menangani Konflik dalam Organisasi Pendidikan: Identifikasi, Tahapan, dan Dampaknya dalam Organisasi - Novi Maulidatur Rosidah; Nafisah Nafisah; Komariyatul Hasanah; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Conflict is an inevitable phenomenon in organizational dynamics. Differences in perceptions, goals and resources often trigger conflict. This research aims to examine the importance of conflict management in maintaining organizational sustainability and performance. Through literature studies, this research concludes that effective conflict management can change destructive conflicts into constructive ones, increase productivity, and strengthen relationships between organizational members. In addition, this research also identifies various conflict management strategies that can be applied in the context of modern organizations. Organizational conflict is a conflict that occurs when the goal-oriented behavior of one group clashes or is threatened by the group's goals.